ANALISA AIR MINERAL MENGGUNAKAN PENGUKUR HAMBATAN BERRBASIS MIKROKONTROLER AT89S51 - Herlina Latipa Sari; Hermawansyah Hermawansyah (Jurnal Media Infotama, 2011)
Analysis of mineral water using AT89S51 microcontroller-based measuring this resistance is a tool designed to analyze the content contained in mineral water on the market in glass packaging. The use of these tools is the electrolysis treatment and precipitate member, then see the results of sediment and analyzed. The results showed the existence of various types of content contained in mineral water on the market with the content of which is a pollutant and an effect on human health. Keyword: Analysis Of Mineral Water